Time Line: Decades of Development Impact: From Colombia to the World - International Center for Tropical Agriculture, CIAT (2025)
Since its founding in 1967, the International Center for Tropical Agriculture (CIAT) has grown from a small team in Colombia into a global research center transforming agriculture for people and the planet. Over the decades, CIAT’s science has helped conserve biodiversity, improve food security, raise smallholder incomes, and restore ecosystems – driven by partnerships, innovation, and a deep commitment to sustainability. This publication presents CIAT’s major milestones, from its founding through 2023.